Exploratory Factor Analysis of Teacher’s Engagement Scale for Early Child Teacher - Cut Ira Dian Sari; Tulus Budi Sulistyo Radikun (Psikostudia : Jurnal Psikologi, 2024)
Teacher engagement is an important factor for teachers to have, which can influence student engagement and student success in the educational process at school. Teacher engagement in this research comes from the student engagement construct, including definitions of behavioral engagement, emotional engagement, and cognitive engagement. This research aims to explore the initial development of the Teacher Engagement Scale specifically for early childhood teachers. This research uses exploratory factor analysis (EFA) method, to see whether the Teacher Engagement Scale items can reflect the construct of teacher engagement. The participants in this research were early childhood teachers with a minimum of 1 year teaching experience. There would be around 230 -245 participants to be involved in this research. The measurement method uses self-report with 4 Likert scales. There are 23 question items in this questionnaire. EFA in this research produces two factors that can explain the construct of teacher engagement. EFA also found that the items from the emotional dimension may not represent that dimension.Teacher engagement atau keterlibatan guru menjadi salah satu faktor penting untuk dimiliki guru, yang dapat mempengaruhi student engagement dan keberhasilan siswa dalam proses pendidikannya di sekolah. Teacher engagement dalam penelitian ini berasal dari konstruk student engagement, meliputi definisi dari behavioral engagement, emotional engagement, serta cognitive engagement. Penelitian ini bertujuan untuk mengeksplorasi pengembangan awal dari Teacher Engagement Scale yang dikhususkan untuk guru anak usia dini. Metode penelitian ini menggunakan analisis faktor eksploratori atau Exploratory Factor Analysis (EFA), sehingga dapat diketahui apakah aitem-aitem Teacher Engagement Scale tersebut dapat mencerminkan konstruk teacher engagement. Partisipan dari penelitian ini adalah guru anak usia dini dengan lama mengajar minimal 1 tahun dan berjumlah sekitar 230 -245 orang. Metode pengukuran menggunakan self-report dengan 4 skala Likert. Total aitem pertanyaan dalam kuisioner ini berjumlah 23 buah. EFA pada penelitan ini menghasilkan dua faktor yang dapat menjelaskan konstruk dari teacher engagement tersebut. EFA juga menemukan bahwa aitem-aitem dari dimensi emosional kemungkinan belum mewakili dimensi tersebut.